2018
DOI: 10.1016/j.adolescence.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Changes to sleep‐wake behaviors are associated with trajectories of pubertal timing and tempo of secondary sex characteristics

Abstract: We examined relations between sleep-wake behaviors and pubertal development from age 8.5 through 15.5 years in a US-based sample of 488 boys (75% White) and 478 girls (78% White). Applying conditional nonlinear growth models to 7-waves of longitudinal data, we examined how sleep-wake behaviors are related to individual differences in the developmental timing and tempo of secondary sex characteristics. For girls, results supported the hypothesis that circadian changes in bedtimes, wake times, sleep duration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 55 publications
7
27
1
1
Order By: Relevance
“…These results support the notion that pubertal development is linked to sleep phenotypes, as the elevation of these hormone levels represents the activation of pubarche [26,37]. Recently, Foley et al reported a prospective association between trajectories in pubertal timing and sleep behavior in a large US cohort [31]; those results are in line with our observation that higher 17-OHP levels were associated with a later sleep timing in our study. We did not identify further associations between plasma hormone levels and sleep timing.…”
Section: Discussionsupporting
confidence: 93%
“…These results support the notion that pubertal development is linked to sleep phenotypes, as the elevation of these hormone levels represents the activation of pubarche [26,37]. Recently, Foley et al reported a prospective association between trajectories in pubertal timing and sleep behavior in a large US cohort [31]; those results are in line with our observation that higher 17-OHP levels were associated with a later sleep timing in our study. We did not identify further associations between plasma hormone levels and sleep timing.…”
Section: Discussionsupporting
confidence: 93%
“…Late adolescent sleep timing has been attributed to environmental factors [ 22 , 23 , 24 , 25 ], but might also be related to endogenous hormonal changes during puberty [ 26 , 27 ]. This hypothesis is supported by rodent studies where gonadectomized rodents showed a shift toward later timings in their day–night activity rhythm [ 28 , 29 , 30 , 31 ]. We therefore examined the association between pubertal development and sleep timing in children with precocious or delayed puberty using validated questionnaires [ 1 , 32 ] and compared those to age- and sex-matched controls.…”
Section: Introductionmentioning
confidence: 81%
“…Daarnaast zullen we ook moeten onderzoeken welke adolescenten gevoelig zijn voor de langetermijneffecten van SM-stress op de slaap en hierbij ook rekening houden met veranderende slaappatronen in de puberteit. Onderzoek toont aan dat het slaappatroon in de puberteit en adolescentie verandert ten opzichte van de kindertijd (Foley et al 2018;Becker et al 2015). Zo blijkt dat het gedurende de puberteit steeds gemakkelijker wordt om tot laat op de avond en in de nacht wakker te blijven en op deze manier het in slaap vallen wordt uitgesteld.…”
Section: Discussieunclassified